The Green Berry Consortia of the Sippewissett Salt Marsh: Millimeter-Sized Aggregates of Diazotrophic Unicellular Cyanobacteria - Wilbanks, Elizabeth G.; Salman-Carvalho, Verena; Jaekel, Ulrike; Humphrey, Parris T.; Eisen, Jonathan A.; Buckley, Daniel H.; Zinder, Stephen H. (Frontiers in Microbiology, 2017)
Microbial interactions driving key biogeochemical fluxes often occur within multispecies consortia that form spatially heterogeneous microenvironments. Here, we describe the “green berry” consortia of the Sippewissett salt marsh (Falmouth, MA, USA): millimeter-sized aggregates dominated by an uncultured, diazotrophic unicellular cyanobacterium of the order Chroococcales (termed GB-CYN1). We show that GB-CYN1 is closely related to “Candidatus Atelocyanobacterium thalassa” (UCYN-A), a globally abundant unicellular diazotrophic cyanobacterium which forms a symbiotic association with eukaryotic algae. Other green berry consortium members include pennate diatoms and putative heterotrophic bacteria from the Alphaproteobacteria and Bacteroidetes. Tight coupling was observed between photosynthetic oxygen production and heterotrophic respiration. In darkness, respiratory activity rapidly depleted oxygen creating anoxia within the aggregates. Metagenomic data revealed a suite of nitrogen fixation genes encoded by GB-CYN1, and nitrogenase activity was confirmed at the whole-aggregate level by acetylene reduction assays. Metagenome reads homologous to marker genes for denitrification were observed and suggest that heterotrophic denitrifiers might co-occur in the green berries, although the physiology and activity of facultative anaerobes in these aggregates remains uncharacterized. Nitrogen fixation in the surface ocean was long thought to be driven by filamentous cyanobacterial aggregates, though recent work has demonstrated the importance of unicellular diazotrophic cyanobacteria (UCYN) from the order Chroococcales. The green berries serve as a useful contrast to studies of open ocean UCYN and may provide a tractable model system to investigate microbial dynamics within phytoplankton aggregates, a phenomenon of global importance to the flux of particulate organic carbon and nitrogen in surface waters.